Implementasi Metode Perbandingan Eksponensial dalam Sistem Pendukung Keputusan Seleksi Mahasiswa Penerima Beasiswa - Muammilul Khair; A. Muhammad Syafar; Darmatasia (AGENTS: Journal of Artificial Intelligence and Data Science, 2022)
Scholarship is one of the programs initiated by the institution that is awarded to a student based on academic achievement or other criteria that may include financial need. Scholarships are awarded selectively in accordance with the scholarships held. The most problem in scholarship program is the selection process to decide scholarship awardees. The conventional selection model in scholarship selection is commonly not transparent and misdirected. This research was conducted in UIN Alauddin Makassar which aims to develop a scholarship selection Decision Support System to facilitate the decision makers in selecting scholarship recipients. The method used in the decision-making process is the Exponential Comparison method. This method is a method with exponential calculation, the difference in value between criteria can be distinguished depending on the ability of the person who judges. The system that has been built is then tested by BlackBox testing. The results of the study show that all features of the system can function properly. This research is expected to facilitate decision makers in selecting scholarship recipients transparently and effectively.